2017
DOI: 10.31276/vjste.59(1).73
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sea level rise for Vietnam East Sea

Abstract: Sea level rise for Vietnam East Sea in the 21 st century was determined under both RCP 4.5 and RCP 8.5 scenarios. Changes in sea level of the Vietnam East Sea due to dynamic and thermosteric processes was estimated using results of different Atmosphere -Ocean General Circulation Model (AOGCMs) under the prescribed method in the IPCC's Fifth Assessment Report (AR5). Changes in sea level due to ice melting and land water storage was determined using a transfer function for global water balance based on the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Eight of 11 papers on HIV/AIDS/sexual health were of good quality and focused on risk factors for HIV (Additional file 4 : Table S3). Six papers discussed migrant fishers’ risk behaviours in Thailand [ 18 23 ], while five papers discussed domestic fishers in Cambodia [ 24 , 25 ], Thailand [ 26 ] and Vietnam [ 27 , 28 ]. Among men who visited sex workers, condom use ranged from 75.6% [ 18 ] to 57% [ 24 ] although different timescales and populations hinder comparability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of 11 papers on HIV/AIDS/sexual health were of good quality and focused on risk factors for HIV (Additional file 4 : Table S3). Six papers discussed migrant fishers’ risk behaviours in Thailand [ 18 23 ], while five papers discussed domestic fishers in Cambodia [ 24 , 25 ], Thailand [ 26 ] and Vietnam [ 27 , 28 ]. Among men who visited sex workers, condom use ranged from 75.6% [ 18 ] to 57% [ 24 ] although different timescales and populations hinder comparability.…”
Section: Resultsmentioning
confidence: 99%
“…Ohnmar et al found that younger age, low education, Mon ethnicity and being in Thailand for longer was associated with penile oil injections among migrant Burmese fishers [ 23 ]. Two studies reported that some fishers were injecting drug users which may be linked to HIV [ 18 , 28 ]. Being a migrant fisher/seafarer was associated with increased odds of ever being tested for HIV in one study [ 22 ], which Ford and Chamratrithirong suggested was linked to knowing someone who’d died of AIDS [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypothetical setting In our choice experiment survey, respondents were presented with a series of scenarios or choice sets of mangrove preservation programs that described the hypothetical market for the attributes. The future climate change scenario (see Appendix) provided by the Ministry of Natural Resources and Environment (MONRE), Vietnam 2 , released in 2016, gave sea level, temperature rise trajectory, and minimum rainfall variation whereas the report by the XTNP's management board provided the estimated rate of mangrove degradation (Tran et al, 2016;Management Board of Xuan Thuy National Park, 2014). Our enumerators demonstrated clearly to respondents what would happen without feasible plans on restoration of mangrove ecosystem.…”
Section: Survey Methodologymentioning
confidence: 99%
“…In some instances, the total annual rainfall has been observed to be more than 20% lower than the long-term average, with certain years experiencing reductions exceeding 30% [24]. In additionally, according to research by Vinh and Huong [25] combined with forecasting models proposed by the Ministry of Natural Resources and Environment of Vietnam [26], drought and water shortage will become more and more serious; specifically, by 2050, there will be no shortage of water. There is still a significant drought area; by 2100, there will be only severe drought in Binh Thuan.…”
Section: The Impact Of Uncertain Factors On Vietnam's Dragon Fruit In...mentioning
confidence: 99%